Pedagog-tarbiyachining kasbiy mahoratini oshirish texnologiyasi - Reymbergenova, D; Sultanova, N; Tleumbetova, Q.D (SCIENCE and SOCIETY, 2023)
This article highlights the benefits of teaching higher education students our ancient traditions and eternal values in combination with the achievements of modern science. Today, in the development of a culture of national dialogue on the basis of pedagogical cooperation, it is necessary to have a thorough knowledge of customs, traditions, national, universal, educational values, our national spiritual heritage. To do this, it is important that the teacher properly organizes communication with students and constantly learns to talk, to communicate. Because it allows the teacher to conduct the lesson effectively. Accordingly, the article scientifically analyzes the importance of the introduction of factors in the development of a culture of national communication in the educational process based on the effective use of methods such as conversation, lecture, storytelling.
Keywords: intelligence; potential; cognitive knowledge; intellectual-cognitive potential; digitization of the educational system; future pedagogues-teachers; theory of intelligence